Behavior Contract Group Counseling For Slow Learner Student Motivation: Konseling Kelompok Kontrak Perilaku Pada Motivasi Belajar Siswa Lamban - Supriadi Supriadi; Suyantiningsih Suyantiningsih (Academia Open, 2026)
General Background Inclusive education requires accommodating diverse academic characteristics to guarantee equitable and quality educational access. Specific Background Individuals with slower cognitive development often experience frequent academic failures that decrease their persistence and overall engagement within mainstream classrooms. Knowledge Gap Prior behavioral interventions primarily address general achievement without specifically integrating peer support and structured agreements to solve these psychological deficiencies in inclusive settings. Aims This Classroom Action Research investigates the application of collaborative interventions combined with written commitments to elevate the academic drive of marginalized adolescents. Results After two intervention cycles involving seven junior high school participants, the average assessment score transitioned from a low category of 34.0 to a high category of 44.4. The participants exhibited observable improvements in persistence, active participation, independence, resilience, and consistency. Novelty This study introduces a structured framework integrating mutual support, individualized reinforcement, and systematic daily monitoring specifically tailored for targeted psychological development. Implications School educators and facilitators should adopt this integrated strategy to cultivate disciplined and responsible habits among diverse populations. Highlights Systematic reinforcement agreements significantly elevate the academic drive of marginalized individuals within inclusive environments. Consistent daily monitoring cultivates persistence, independence, and active educational participation. Structured peer support frameworks translate abstract expectations into concrete scholastic commitments. Keywords Behavior Contract; Group Counseling; Learning Motivation; Slow Learner; Inclusive Education